Anti-diabetic activity of red pitaya (Hylocereus polyrhizus) fruit - Omidizadeh, Alireza; Mohd Yusof, Rokiah; Roohinejad, Shahin; Ismail, Amin; Abu Bakar @ Zakaria, Md Zuki; Bekhit, Alaa El-Din A. (Royal Society of Chemistry, 2014)
This study investigated the anti-insulin resistant activity of red pitaya (Hylocereus polyrhizus) fruit. Fresh pitaya along with two heat-processed pitaya samples with different proportions of phenolic contents, scavenging activities, and soluble dietary fibers were tested in insulin resistant rats over 6 weeks of treatment in a cause-effect study to investigate the anti-insulin resistant components of red pitaya. The results showed that fresh pitaya significantly (p < 0.05) attenuated the insulin resistance, hypertriglyceridemia and atherosclerotic changes induced by fructose supplement in rats. Thermally-treated pitaya at 95 °C for 30 min (containing a low antioxidant content) significantly (p < 0.05) improved hyperinsulinemia. Thermally-treated pitaya at 105 °C for 60 min (containing a low antioxidant and soluble dietary fiber content) fed to rats had no significant effect on insulin resistance, dyslipidemia and atherogenesis. Based on this study, the anti-insulin resistant effect of red pitaya can be attributed to its antioxidant and soluble dietary fiber contents.